Life histories and evolution: insights from notothenioids (Teleostei, Perciformes) - Riginella, Emilio (Università degli studi di Padova, 2015)
ABSTRACT Organisms show an extraordinary variation in their life history traits, both at inter- and intraspecific level, exhibiting phenotypic variations among populations inhabiting different habitat. The variability in life history traits has been related to environmental conditions, as a result of selective processes or phenotypic response to them. In addition to the huge diversity in life history traits, several trade-offs among them have been recognized. The variability in life history traits and in their trade-offs related to environmental conditions represents a key aspect in the study of evolutionary processes. A wide variation in life history traits is documented among teleost fishes, both among and within species, reflecting the effects of evolutionary forces acting on them over time and across environmental conditions. Several life history traits, such as growth rate, age at sexual maturity, fecundity, reproductive investment, egg size, hatching size, are strongly influenced by temperature and food availability. Notothenioid fish represent a unique example of fish adaptive radiation in marine environment. They dominate the waters surrounding the Antarctic continent both by species number, with over 120 species (47%), and biomass (90-95%). Notothenioids distribution is limited exclusively to the Antarctic and sub-Antarctic regions (South America, New Zealand and South East Australia). Variability in their life history traits at inter- and intra-specific levels has been described, with a latitudinal trends in some reproductive traits. In this framework, despite the availability of recent phylogenies of notothenioids, a comparative analysis aimed at studying habitat dependent evolution of reproductive strategies has not yet been performed. Given the particular characteristics of their habitats and the uniqueness of notothenioid fishes, they can be considered an excellent taxon model to investigate the evolution of life history traits in relation to environmental factors. The aim of this PhD project was ...